Jelaskan wadah perbaharu tekad : pesanan buat generasi muda Islam - Anwar Ibrahim, Dato' Seri, 1947- (Kuala Lumpur : Penerbitan Ilham Baru, 2010)
Collected speeches of Anwar Ibrahim on Islamic and political development in Malaysia.
Keywords: Anwar Ibrahim, -- Dato' Seri, -- 1947- -- Political and social views; Angkatan Belia Islam Malaysia -- Political and social views; Islamic sociology -- Malaysia